The Tablighi Jamaat Movement Its Ideological Concept and Organizational Structure - Zulkhan Indra Putra (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
The author discusses the nature of the Tablihi Jamaat, an India-based Islamic movement which in the past decades has witnessed organizational transformation by becoming the transnational Islamic movement active in many parts of the world. The author pays attention to the characteristic of religious ideology of the organizational pattern of Tablighi Jamaat. He argues that a strong organizational commitment and voluntarism among the members of the Tablighi Jamaat have had a profound impact on the enduring Tablighi Jamaat activities. Yet, ideologically, unlike other Islamic movements such as Ikhwanul Muslimin or Hizbut Tahrir whose ideological foundations are nurtured through written communication and speech based-congregational preaching, the Tablighi Jamaat has utilized direct and personal approach in delivering the messages of Islam to the communities. Keywords: Tablighi Jamaat, religious Ideology, transnational organization, the Islamic movement.